2009
DOI: 10.1158/1541-7786.mcr-09-0138
|View full text |Cite
|
Sign up to set email alerts
|

The Aberrant Localization of Oncogenic Kit Tyrosine Kinase Receptor Mutants Is Reversed on Specific Inhibitory Treatment

Abstract: Kit is a cell surface type III tyrosine kinase (TK) receptor implicated in cell transformation through overexpression or oncogenic mutation. Two categories of Kit mutants displaying mutations either in the juxtamembrane intracellular domain (regulatory mutants) or in the catalytic domain (catalytic mutants) have been described. To explore the effect of Kit oncogenic mutations on its subcellular localization, we constructed enhanced green fluorescent protein (EGFP)-tagged human Kit chimeras harboring mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 50 publications
6
50
2
1
Order By: Relevance
“…2 A and B, the presence of WT KIT and the N505I mutant on the cell surface is higher than that of T417IΔ418-419 and Dup A502Y503 mutants. The presence of the cytoplasmic domain mutants V560D, D816V, and V560DY823D on the cell surface was very low, in accordance with previous reports (18,19). We also used fluorescence microscopy to visualize the cellular distribution of a green fluorescent protein (GFP) fused to WT or each oncogenic KIT mutant expressed in COS7 cells.…”
Section: Kit Cellular Distribution and Dynamic Properties Are Affectesupporting
confidence: 83%
See 2 more Smart Citations
“…2 A and B, the presence of WT KIT and the N505I mutant on the cell surface is higher than that of T417IΔ418-419 and Dup A502Y503 mutants. The presence of the cytoplasmic domain mutants V560D, D816V, and V560DY823D on the cell surface was very low, in accordance with previous reports (18,19). We also used fluorescence microscopy to visualize the cellular distribution of a green fluorescent protein (GFP) fused to WT or each oncogenic KIT mutant expressed in COS7 cells.…”
Section: Kit Cellular Distribution and Dynamic Properties Are Affectesupporting
confidence: 83%
“…We and others (18,19) have shown that glycosylated WT KIT migrates on SDS/PAGE as two distinct bands with apparent molecular masses of 145 kDa and 125 kDa ( Fig. 2 C and D).…”
Section: Kit Cellular Distribution and Dynamic Properties Are Affectementioning
confidence: 61%
See 1 more Smart Citation
“…Furthermore, the cellular localization of MT-KIT differs from that of WT-KIT and is not fully understood. Most WT-KITs are localized to the plasma membrane before ligand binding, but some MT-KITs are abnormally localized to the intracellular compartment (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…De plus, les formes immatures de KIT peuvent être phosphorylées et transmettre un signal d'activation cellulaire ( Figure 5). Des résultats similaires ont été obtenus par d'autres équipes [31]. Les formes mutées et sauvages de KIT ayant des devenirs biologiques très différents, et les GIST coexprimant les deux formes, il nous a semblé important d'étudier la biologie des formes mutées de KIT en comparant leur expression isolée et leur coexpression avec les formes sauvages.…”
Section: Biochimie Des Formes Mutées Et Sauvages De Kitunclassified